Emergency Department Use by Terminally Ill Patients: A Systematic Review - Amado-Tineo, José P. (2021)
Context: Terminally ill patients (TIP) frequently visit the emergency department (ED), but the prevalence of these visits is unclear. Objective: To determine the prevalence of TIP visiting the ED. Methods: Systematic review of observational studies published between 1998 and 2018 reporting adults TIP who used the hospital ED, searching in PubMed, CINAHL, SciELO, LILACS, and Cochrane. Three evaluators selected and extracted data (kappa concordance 0.63). The quality of the studies was evaluated with the Newcastle–Ottawa scale and global estimates were made, calculating combined prevalence (95% confidence interval [CI]) and heterogeneity of the studies (I2). Results: We identified 2429 publications, ultimately including 31 studies in 14 countries; 79% were from high-income countries, 21% from medium-income countries, and none from low-income countries. Most were from 2015. We found that 45% of patients with cancer visited the ED in the last month of life [95% CI 37–54%] and 75% in the last six months of life [95% CI 62–83%]; I2 = 100%. Overall, 17% of patients who visited the ED had a terminal illness [95% CI 12–23%]; I2 = 98%. Few studies reported terminal nononcologic illness, specific age groups or diseases, hospital admission rates, use of palliative care or nonresuscitation, or other criteria that could be used for grouping. Conclusions: Patients with terminal cancer frequently use the ED at the end of life, although use varies among patients and few studies have examined low-income countries or patients with nononcologic terminal illness. The global prevalence of TIP in the ED cannot be calculated from limited reports.